Training in Writing and Publication of Scientific Articles for Teachers-Primary school teachers - Fajariyah Akbari, Ummu (Teumulong: Journal of Community Service, 2023)
Writing articles and scientific publications is a form of teacher professional development that can contribute to improving the quality of teaching in the teaching and learning process. However, the number of research articles produced by professional teachers is still small. The obstacles experienced by teachers when writing scientific articles are developing ideas or thoughts into coherent and coherent scientific writing, understanding regarding the mechanisms of classroom action research that must be carried out to start writing scientific articles is still quite low. Producing scientific work and scientific publications is one part of the professional competence that teachers must achieve. However, not all teachers have this competency. For this reason, it is necessary to carry out training in writing scientific articles and publishing them as an effort to increase teacher competency and also to fulfill credit score requirements related to promotion and teacher certification. Sikka State Madrasah Ibtidaiyah teachers are the target participants in implementing this training. The method for this service is In Service Training (IST) through lectures, discussions and presentations. As a result of this service, participants understand the concept of research papers and can write research papers that are ready to be published in accredited national journals. This activity was said to be successful because participants' understanding of the material increased, participants' reactions to the activity were very positive.